Relación Entre Prácticas Parentales Y El Nivel De Asertividad, Agresividad Y Rendimiento Académico En Adolescentes - Fragoso, Claudia González; Benítez, Yolanda Guevara; Rodríguez, David Jiménez; Olán, Raúl J. Alcázar (European Scientific Journal, ESJ, 2017)
The behaviors that parents use to educate their adolescent children can influence various aspects of their psychosocial performance, either by promoting the development of behavioral skills or by associating with behavioral problems, aggressiveness or depressive and anxious symptoms. The objective of the study was to know the relationship of parental practices with the level of assertiveness, aggressiveness and academic performance in a sample of young Mexican adolescents. Participated 565 students of a Mexican public secondary, with an average age of 13.01 years. Two instruments, the Parental Practice Scale for Adolescents (Andrade & Betancourt, 2008) and the Assertive Behavior Scale (Michelson & Wood, 1982) were applied individually, in addition, the students' average school grades were obtained. Mean scores indicated aggressive behavior patterns throughout the sample, significantly higher in males (p <.05). The maternal practices of Communication, Autonomy, and Behavioral Control correlated with the level of assertiveness in the young, and with their school average; both indicators, significantly higher in adolescent females compared to males. Paternal practices correlated with the level of assertiveness and aggressiveness in males.